2020
DOI: 10.1037/edu0000449
|View full text |Cite
|
Sign up to set email alerts
|

The relative effectiveness of different active learning implementations in teaching elementary school students how to design simple experiments.

Abstract: “Active learning” has been used to describe classrooms that have varied widely with respect to instructional topics, age of learners, and the procedures used to operationalize the general notion of the term. In most cases, the specific variant of active learning under investigation has been more effective than the particular control used for comparison. The goal of the current study was to unambiguously describe, implement, and assess 4 different active learning implementations that varied based on the instruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Nevertheless, lecture is not necessarily ineffective in that it can be an efficient way to disseminate information (see research on explicit/direct instruction, for example (e.g., Klahr & Nigam, 2004; Martella et al, 2020). Lectures have the potential to provide context and structure for a subject, facilitate the development of an idea, promote listening and note-taking skills, give students access to new information in the field, and allow students to learn from content experts in the field, among other possible benefits (French & Kennedy, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, lecture is not necessarily ineffective in that it can be an efficient way to disseminate information (see research on explicit/direct instruction, for example (e.g., Klahr & Nigam, 2004; Martella et al, 2020). Lectures have the potential to provide context and structure for a subject, facilitate the development of an idea, promote listening and note-taking skills, give students access to new information in the field, and allow students to learn from content experts in the field, among other possible benefits (French & Kennedy, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, in the sixth question a fairly high percentage (80%) of teachers answered between the options "Moderately" and "Very" (Tables 8 and 9). This means that the respondents' statements are positive regarding the fact that the educational needs and interests of students are met in the best possible way through the use of experiential -participatory teaching techniques.In line with the data of questions ( 5) and (6) in several researches and studies, it is demonstrated that the utilization of experiential -participatory teaching techniques achieve active participation in the learning process by taking into account the needs and interests of students (Barta et al, 2022;Evangelou, 2023a;Hackathorn et al, 2011;Martella et al,2020;Linsenmeyer, 2021;Lombardi et al,2021;Vosniadou et al, 2020;Wolff et al, 2015;Yennita & Zukmadini, 2021).…”
Section: Discussionmentioning
confidence: 57%
“…From the literature review, it is found in numerous researches and studies that experientialparticipatory teaching techniques, when utilized during the learning and teaching process, arouse the interest of students and achieve their active participation in the learning process (Chugai et al, 2017;Hackathorn et al, 2011;Koutsoukos et al, 2021;Lygda et al, 2021;Martella et al,2020;Wolff et al, 2015;Zayapragassarazan & Kumar, 2012) taking into account students' needs and interests (Barta et al, 2022;Evangelou, 2023a;Linsenmeyer, 2021;Lombardi et al, 2021;Vosniadou et al, 2020;Yennita & Zukmadini, 2021), enhance student learning, contribute to high learning outcomes (Armbruster et al, 2009;Barta et al, 2022;Evangelou, 2023a;Hyun et al, 2017;Johnson et al, 2014;Johnson & Johnson, 2017;Linsenmeyer, 2021;Rissanen, 2014;Sakata, 2022;Slavin, 1985Slavin, , 2015Surakarn et al, 2020;Termos, 2013), as well as improve social relationships among work group members in the classroom through interaction and collaboration among students (Courau, 2000;Evangelou, 2023a;Kaldi et al, 2009aKaldi et al, , 2009bKaldi et al 2011;Kaldi, 2014;Louizou et al, 2019;Surakarn et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nguyen et al (2021) define active learning as, "classroom-based activities designed to engage students in their learning through answering questions, solving problems, discussing content, or teaching others, individually or in groups" (2). This common approach that active learning is activity driven aligns with one of the currently most cited definitions (see Martella, Klahr, and Li 2020) from Freeman et al (2014): "Active learning engages students in the process of learning through activities and/or discussion in class, as opposed to passively listening to an expert" (8413). In addition to activity-driven ones, definitions emphasizing engagement are also common: "The core elements of active learning are student activity and engagement in the learning process" (Prince 2004, 223).…”
Section: Introductionmentioning
confidence: 76%